ANALISIS IMPLEMENTASI PERATURAN DAERAH KABUPATEN SERANG NOMOR 3 TAHUN 2019 TENTANG PENGELOLAAN PERSAMPAHAN (STUDI KASUS DI PASAR CIRUAS KABUPATEN SERANG) - Lutfiah, Jihan; Bangsawan, Try Adhi; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study stems from the issue of environmental pollution related to waste. Proper waste management will become a serious problem in the future, because environmental sustainability is also affected by waste issues. Global concern regarding environmental damage is inevitable, thus affecting climate change that is difficult for countries around the world to avoid. This study aims to determine the implementation of Serang Regency Regulation Number 3 of 2019 concerning Waste Management at Ciruas Market in Serang Regency. The research method used in this study is qualitative with a descriptive approach to provide an overview of how the regional regulation is implemented at Ciruas Market. This study uses Edward III's theory on policy implementation. The results of the study show that, in general, the Serang Regency local government has made efforts to implement the Regional Regulation on Waste Management. However, it has not achieved maximum results. Therefore, efforts and commitment are needed to address the waste problem. Furthermore, the implementation of this local regulation faces obstacles in terms of facilities and infrastructure, human resources, and public awareness regarding waste reduction. Even though there are supporting factors, where the local government has designated waste issues as a strategic program in Serang Regency.